Environmental reporting, financial fundamentals and company valuation: Insights from the industrial sector - Dan Gabriel Dumitrescu; Ştefania-Cristina Curea; Cristiana Ioana Coman; Anca Gabriela Ilie; Renate Bratu; Alma Pentescu (Amfiteatru Economic, 2025)
The paper investigates the effect of environmental policies on the market valuation of companies within the European Union's Industrial sector, along with traditional financial indicators. Taking into account the Corporate Sustainability Reporting Directive imposed by the European Union authorities for the most prominent companies, we used a comprehensive data set of 494 publicly listed companies over the period 2020-2023 to assess the predictive impact of environmental policy adoption (EPO), environmental policy quality scores (EPOS), and financial variables (FV) on the price-to-book (PB) ratio of listed companies. We use a Random Forest regression model to identify and rank the importance of a comprehensive set of variables, underlining the idea of investor attention and priorities. The main findings point to an increase in investor interest in the effectiveness of environmental policies rather than their simple presence, emphasising the strategic importance of integrating measurable environmental outcomes into company valuation frameworks. However, traditional financial variables consistently outperform environmental indicators in explaining market valuation.
Keywords: G32; Q56; M14; C55; 330; environmental policies; market valuation; random forests; CSRD